Propuesta para reformar la ley 100 de 1993 (1998)
ABSTRACT: The proposal describes why Law 100 de 1993 must be reformed, it analyzes some structural aspects such as the performing actors, the quality guarantee and solutions to some epidemiological problems. The social context is analyzed for an integral reform and guidelines are suggested. The differentiation between promotion and prevention is done from an operational, administrative and financial point of view, and a minimum portfolio of health promotion is defined. Finally, the role of the State is indicated in activities of public health surveillance and in the formulation of public policies cooperating to intersectorial actions.